SOCIAL INVESTMENT AND POVERTY REDUCTION: EDUCATIONAL ADVANCEMENT OF N-TEACH BENEFICIARIES IN BORNO STATE, NIGERIA - Abiso, Ali; Mohammed, Babagana; Alhaji Kunduli, Modu (African Journal of Social and Behavioural Sciences, 2026)
Poverty remains a persistent and complex global challenge affecting millions in both developed and developing countries. Despite years of economic growth, policy reforms, and international development efforts, many people still live below acceptable standards of living. To address this problem, the National Social Investment Programme (NSIP), including initiatives such as N-Power and N-Teach, was introduced to promote human capital development and poverty reduction. This paper examines Social Investment and Poverty Reduction: Educational Advancement of N-Teach Beneficiaries in Borno State, Nigeria. The research design is Survey research, and the Sampling Technique is multistage sampling, which comprises cluster and simple random Sampling. A total of 392 Questionnaires were distributed to the respondents, and 384 were retrieved and used for the analysis. Descriptive statistics and regression analysis were used to present and analyse the data. The results indicate that the programme has a strong positive impact on beneficiaries’ willingness to continue their studies, reduces turnover rates, promotes the development of entrepreneurial skills, and enhances working experience and workability. The regression model shows that N-Teach is positively and significantly related to educational advancement. The paper concluded that the N-Teach Programme enhances the educational advancement of beneficiaries in Borno State and recommends that the Federal Government should provide organised exit strategies, such as entrepreneurship and job placement services, to make the beneficiaries economically sustainable in the long term.